2018
DOI: 10.1111/bcp.13570
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine and Z‐drug prescribing in Ireland: analysis of national prescribing trends from 2005 to 2015

Abstract: Benzodiazepine prescribing to the GMS population in Ireland decreased significantly from 2005 to 2015, and was coupled with significant increases in Z-drug prescribing. The study shows that benzodiazepine and Z-drug prescribing is common in this population, with high proportions of individuals receiving long-term prescriptions. Targeted interventions are needed to reduce potentially inappropriate long-term prescribing and use of these medications in Ireland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 41 publications
9
52
0
3
Order By: Relevance
“…Estudios poblacionales recogen la tasa de prescripción de estos fármacos en diferentes países, observándose una amplia variabilidad. En Irlanda, la tasa en mayores de 16 años fue 16,6 % (IC 95 %: 16,5-16,7 %) en 2015 (30). En un estudio realizado en Suiza, el 9,1 % de los adultos encuestados (n = 45.309) habían recibido al menos una prescripción en un periodo de 6 meses (31).…”
Section: Resultsunclassified
“…Estudios poblacionales recogen la tasa de prescripción de estos fármacos en diferentes países, observándose una amplia variabilidad. En Irlanda, la tasa en mayores de 16 años fue 16,6 % (IC 95 %: 16,5-16,7 %) en 2015 (30). En un estudio realizado en Suiza, el 9,1 % de los adultos encuestados (n = 45.309) habían recibido al menos una prescripción en un periodo de 6 meses (31).…”
Section: Resultsunclassified
“…Many surveyed general practitioners also perceived Z-drugs as more effective and safer compared w i t h b e n z o d i a z e p i n e s [ 1 6 ] . I n a d d i t i o n , pharmacoepidemiological studies report a reduction of benzodiazepine prescribing while Z-drug prescribing is increasing [19]. Z-drugs still seem to benefit from the myth that they are similarly effective and safer alternatives to benzodiazepines, although studies show that Z-drugs also carry the same risks of daytime sedation, cognitive impairment, falls, fractures, and accidents [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature on duplicated tramadol use is sparse, one study found that the 1‐year incidence rate of tramadol shopping behaviour was 1.0% (95% CI 0.7‐1.5) in France . Another study showed that the therapeutic duplication rate of NSAID/analgesic prescriptions in Korea was 13.3%, and a third study found that 2.7% of Z‐drug users in Ireland received duplicate prescriptions …”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we distinguished ED from duplication by ruling out accidentally overlapped prescriptions. By excluding those with less than 10% duplication during the total prescription period from the ED group, we tried to provide a more clinically significant definition of duplication of tramadol use than previous studies which defined one day or more of overlapping as duplication . Also, we identified factors that could affect tramadol use, including patients’ age and special comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation